2021
DOI: 10.1002/adfm.202105820
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐High Alignment of Polymer Semiconductor Blends Enabling Photodetectors with Exceptional Polarization Sensitivity

Abstract: Photodetectors that can sense not only light intensity but also light's polarization state add valuable information that is beneficial in a wide array of applications. Polymer semiconductors are an attractive material system to achieve intrinsic polarization sensitivity due to their anisotropic optoelectronic properties. In this report, the thermomechanical properties of the polymer semiconductors PBnDT‐FTAZ and P(NDI2OD‐T2) are leveraged to realize bulk heterojunction (BHJ) films with record in‐plane alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Of interest are some donor‐acceptor low bandgap polymers such as poly(benzodithiophene‐alt‐dithienyl difluorobenzotriazole) used for instance in polarized photodetectors. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest are some donor‐acceptor low bandgap polymers such as poly(benzodithiophene‐alt‐dithienyl difluorobenzotriazole) used for instance in polarized photodetectors. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…Of interest are some donor-acceptor low bandgap polymers such as poly(benzodithiophene-alt-dithienyl difluorobenzotriazole) used for instance in polarized photodetectors. [43] A simple and versatile method combining rubbing and annealing can be used to fabricate smooth polymer films with controlled orientation and crystal dimensions. In the present study, it has been used to prepare PLA films with controlled surface texture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Table S1, Supporting Information, summarizes the detectivity and R ∥ /R ⊥ of polarization-resolved low-dimensional and organic photodetectors reported to date. [13,16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] To the best of our knowledge, our devices exhibit the best detectivity (>10 12 Jones), and it is worth mentioning other merits like LDR and f −3 dB are among the best-performed polarization-resolved photodetectors.…”
Section: Polarization-resolved Organic Photodetectorsmentioning
confidence: 99%
“…Recently, Conner group successfully aligned poly(benzodithiophene fluorinated benzotriazole) (PBnDT‐FTAZ) donor and poly(naphthalene diimide‐alt‐bithiophene) (N2200) acceptor blend film by combing mechanical rubbing and annealing processes, and subsequently achieved a polarization‐resolved photodetector. However, they found that it is difficult to obtain high responsivity and polarization sensitivity at the same time, [ 13 ] because the rubbing process scratches the film surface and thus deteriorates the device performance. Uniaxial straining is another alternative method to reorient the film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation